Magnum streetwise - McLaren, Stephen (Thames & Hudson, 2019)
Ambitious in scope, democratic in nature, 'Magnum Streetwise' is an unmissable tour through the photographs and practices that have helped define what street photography is and can be. Magnum photographers such as Henri Cartier-Bresson pioneered "modern" concepts of street photography before the term was even coined. But their influence is far from historic. A rich seam of street photography runs through the heart of Magnum to this day, both in the work of recognized masters of street photography - such as Erwitt, Parr, Gilden and Kalvar - and of those who might not even consider themselves street photographers; a continued influence that has not gone unnoticed among the current generation of budding street photographers and fans. 0'Magnum Streetwise' is a true visual feast, interleaving insightful texts and anecdotes within an intuitive blend of photographer- and theme-based portfolios, exploring not only the work of outstanding photographers, but how common subject matter (places of leisure, marketplaces, travel) and locations (Paris, New York, Tokyo) have been addressed, conceptually and practically, across the agency and through the ages. Magnum Streetwise is an essential addition to the bibliography of street photography, showcasing hidden gems alongside many of the genre's most famous images
Titelzusatz auf dem Cover: The ultimate collection of street photography
Keywords: Magnum Photos Inc.; Öffentlicher Raum -- Motiv; Fotografie; Streetphotography; Street photography; Photography, Artistic; Bildband